Modeling granule-based completely autotrophic nitrogen removal over the nitrite (CANON) process in an SBR. Issue 1 (24th August 2021) - Cai, Qing; He, Qiang; Zhang, Sheng; Ding, Jiajia
Abstract: Based on the simplified activated sludge model No. 1 (ASM1), a 1D biofilm model containing autotrophic and heterotrophic microorganisms was developed to describe the microbial population dynamics and reactor dynamics of completely autotrophic nitrogen removal over the nitrite in sequencing batch reactor (CANON SBR). After sensitivity analysis and calibration for parameters, the simulation results of NH4 + -N concentration and NO2 − -N concentration were consistent with the measured results, while the simulated NO3 − -N concentration was slightly lower than the measured. The simulation results showed that the soluble microbial products had an extremely low concentration. The aerobic ammonia oxidation bacteria and anaerobic ammonia oxidation bacteria were the dominant microbial populations of the CANON system, while nitrite oxidization bacteria and heterotrophic bacteria were eliminated completely. The optimal ratio of air aeration load to influent NH4 + -N load was about 0.18 L air/mgN. The operating condition of the reactor was optimized according to the simulation results, and the total nitrogen removal rate and the total nitrogen removal efficiency increased from 0.312 ± 0.015 to 0.485 ± 0.013 kg N/m 3 /d and from 71.2 ± 4.3 to 85.7 ± 1.4%, respectively. HIGHLIGHTS: The microbial population dynamics and the reactor dynamics model were developed. The model parameters were calibrated using the long-term operational data. The SMP had an extremely low concentration. The aerobic ammonia oxidation bacteria and anaerobic ammonia oxidation bacteria are dominant, while the nitrite oxidization bacteria are eliminated.